Akuntan Publik: Daya Tarik dan Faktor Pendorong Minat Mahasiswa - Fauzi, Restu Ismail; Hardiningsih, Pancawati (Universitas Batanghari Jambi, 2024)
This research aims to analyze the influence of financial rewards, work environment, job market considerations, and artificial intelligence knowledge on accounting students' interest in choosing a public accounting career. Sampling using a convenience purpose sampling technique obtained 105 respondents. The research results show that the variables of financial rewards and labor market considerations show a significant positive influence. Students' knowledge of artificial intelligence provides significant positive results, meaning that the higher their knowledge of artificial intelligence (AI), the greater their interest in a career as a public accountant. Meanwhile, work environment variables have no effect on students' interest in pursuing a career as a public accountant, this happens because students do not prioritize risks or things gained in the work environment.